An unusual cause of acute upper gastrointestinal obstruction in a child. A case report - Abd. Aziz, Azian; Govindarajan, Krishna Kumar; KRA, Mohanaprakash (2011)
A 9 month old boy was admitted to our hospital with sudden onset of bilious vomiting. Nothing remarkable was detected on physical examination and his abdomen was not distended. The laboratory investigations were within normal limits. Abdominal radiograph showed prominent gastric shadow with paucity of bowel gas distally. Contrast study of the upper gastrointestinal tract revealed a paucity of contrast flow beyond the proximal jejunum with a ‘claw’ sign, which appear like an intussusception. Ultrasound abdomen performed at the same time did not demonstrate the usual appearance expected of an intussusception but revealed a well-defined fluid-filled ‘mass’. A radiological diagnosis of intestinal obstruction from a possible bowel duplication cyst was made and child was taken for surgery. Intra operatively, a firm mobile mass was felt in the jejunum and following enterotomy, two firm jelly-like foreign bodies were seen blocking the jejunal lumen causing obstruction. Mother later recalled that her older son had miniature toy in shapes of various animals which will expand to twice or triple the original size when submerged in water. She then remembered that her 9 months old child was seen playing with these and realized he might have swallowed them. The child had an uneventful post operative recovery and was discharged home well. Parents should be aware and cautious about this kind of toys which manufacturers called “growing toys / creatures”, which are made of hydrophilic polymer called hydrogel. In most countries these types of toys have been banned.